PERUBAHAN PASAR SEBAGAI AKIBAT PERUBAHAN PERILAKU KONSUMEN PERGESERAN PARADIGMA PEMASARAN DAN IMPLIKASI TERHADAP STRATEGI PEMASARAN PENDEKATAN TEORI 3 GELOMBANG PERUBAHAN ALFIN TOFLER - Salenussa, Stanley (Fokus Ekonomi, 2006)
Globalization, which is signed by technological, financial, and information democratization, becomes a frightening jargon in human life today. The organization purpose is no longer to create products for customers, but it is to create a value for the customers. This creation will result in marketing paradigm movement and implementation for organization strategy. This paper presents changes in consumer behavior of theoretic perspective of Tiga Gelombang Perusahaan Ariffin Toffler and implication for current marketing, in line with change movement from first wave to third wave.Keywords: Change, Marketing Strategy